A preliminary study on assessment of lead exposure in competitive biathletes: and its effects on respiratory health - Turmel, J.; Bougault, V.; Couture, J.; Boulet, L.-P. (Movement & Sport Sciences - Science & Motricité, 2022)
Aim: In this preliminary study, we aimed to assess the blood lead level (BLL) in biathletes compared to cross-country skiers, and to look at the effects on airway function, responsiveness, allergic sensitization and the report of training-induced respiratory symptoms. Methods: Eleven biathletes (19 ± 2 years old, sex: 6M:4F) and 12 cross-country skiers (18 ± 3 years old, sex: 4M:8F) had a blood sample, spirometry, bronchial provocation test to Methacholine, skin prick tests, and induced sputum. Biathletes performed the tests within 3 h after a 90 to 120 min shooting session (150 ± 45 bullets fired). Results: Lung function, airway responsiveness, sensitization to common airborne allergens, and the report of training-induced respiratory symptoms were not different between both groups of winter sport athlete. BLL was significantly higher in biathletes vs. cross-country skiers (geometric mean [95%CI]: 2.15 [1.37-2.94] µg/dL vs. 0.85 [0.81-0.89] µg/dL, respectively, p < 0.001, Cohen`s d = 1.25). One biathlete had a BLL greater than the recommended threshold (> 5 µg/dL). Significant correlations were observed in biathletes only between BLL and FEV1 and FVC in absolute value (r = 0.69, p = 0.02 and r = 0.69, p = 0.02, respectively). Conclusion: Despite higher BLL in biathletes, no difference in atopy, respiratory function or symptoms was observed with cross-country skiers in our experimental conditions.